1988
DOI: 10.1042/bj2530603
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tumour-bearing on 2-deoxy[U-14C]glucose uptake in normal and neoplastic tissues in the rat

Abstract: The extent to which normal and neoplastic tissues of the rate take up glucose was assessed by the 2-deoxy[U-14C]glucose tracer technique. Measurements of glucose uptake were made over 40 min in anaesthetized rats under conditions where the blood glucose concentration was constant. In fed tumour-bearing rats, the relative rates of glucose uptake per g wet wt. of tissue were tumour (100), small intestine (72), brain (61), heart (61), spleen (50), lung (42), adipose tissue (11) and muscle (8). Normal tissues of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…For ethical reasons, we have not examined the effects of tumour size on survival. While DAMA has been reported to be oestrogen receptor-negative (13) and our initial studies indicated similar growth in male and female rats (14), closer examination has shown increased tumour size in female rats under identical conditions of inoculation. Therefore its hormone sensitivity requires further investigation.…”
Section: Morphologymentioning
confidence: 47%
See 1 more Smart Citation
“…For ethical reasons, we have not examined the effects of tumour size on survival. While DAMA has been reported to be oestrogen receptor-negative (13) and our initial studies indicated similar growth in male and female rats (14), closer examination has shown increased tumour size in female rats under identical conditions of inoculation. Therefore its hormone sensitivity requires further investigation.…”
Section: Morphologymentioning
confidence: 47%
“…The appearance of marked ketonaemia following fasting in this model has been discussed in detail elsewhere (12) and indicates an increased dependence by normal tissues in tumour-bearing rats on fat-based fuels. We have also observed that the insulin-independent tumour competes with the host for blood glucose and therefore grows at the expense of host tissue (14). This effect is exacerbated by the presence of insulin resistance in the host and a reduction in the level of circulating insulin (13.14).…”
Section: Morphologymentioning
confidence: 89%
“…28 In this setting it has been found that the DA-specific mammary adenocarcinoma will sequester four times more glucose than muscle. 38 The combination of rapid growth of the tumor, preferential glucose usage and the upregulated release of cytokines into the periphery from the tumor, may pose problems systemically and to organs such as the gut. Potentially, this may lead to deleterious effects on other organs when combined with MTX treatment, whereby healing and repair of epithelial tissues could be inhibited significantly.…”
Section: Discussionmentioning
confidence: 99%
“…The mammary adenocarcinoma used in this DAR (DAMA) model arose spontaneously in the 1970s. 28,37,38 This cancer cell line was kindly donated by Drs. A. Rofe (IMVS, Adelaide, Australia) and R. Gibson (Hanson Institute, IMVS, Adelaide, Australia).…”
Section: Discussionmentioning
confidence: 99%
“…Low tumour glucose levels are exacerbated because tumour cells preferentially metabolise glucose by either aerobic or anaerobic glycolysis, rather than by oxidative phosphorylation (Warberg, 1956). This is thought to be due to gene mutations influencing the expression of the key regulatory enzymes of glycolysis (Vora et al, 1985;Hue and Rousseau, 1993;Chesney et al, 1999), which results in increased glucose utilisation rates per gram of tissue (Rofe et al, 1988;Heacock and Sutherland, 1990).…”
mentioning
confidence: 99%